Potency and Carrying Capacity of Rice Straw for Beef Cattle Feeding in East Kalimantan - H. Mayulu; Suhardi Suhardi (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
Utilization of rice straw instead of green fodder is very potential to meet the scarcity of green fodder in the dry season. Low nutrient content and bulky characteristic of rice straw can be anticipated through treatment. Optimal utilization of rice straw provides opportunities for a waste-free production concept of low external input sustainable agriculture (LEISA). The research was conducted in two stages: 1) survey using purposive sampling techniques to determine the potential quantity of rice straw in three districts; and 2) a laboratory experiment, aimed to determine the potential nutritional quality of rice straw. Surveys in the form of data collection on the extent of paddy rice crops, the number of beef cattle population as the basis for determining the carrying capacity of rice straw in providing the feed. Laboratory experiments included sample preparation of rice straw through the enumeration, drying, determination of dry matter (DM), and proximate analysis. The results showed that average yield of rice straw in the area of research during the last five years was +9.799; +8.302; +7.079; +8.714; and +6.432 tons/year, respectively. The average population was 1.264, 1.616, 1.842, 1.683, and 1.919 animal unit (AU)/year, respectively. The average feed requirement for beef cattle was 44.609, 23.719, 20.225, 24.897, and 18.377 tons/year, respectively. On the average, carrying capacity per year was 54.07, 78.91, 20.16, 65.91, and 16.58 AU/year, respectively. Chemical composition of rice straw according to proximate analysis was DM=87.85%, crude protein=4.86%, ether extract=0.91%, crude fibre = 41.07%, Nitrogen free extract = 36.98%, and Total digestible nutrient = 46.65%. In conclusion, in terms of quantity and quality, rice straw has the potential to meet the needs of beef cattle feed in Penajam Paser Utara, Kutai Kartanegara and Berau.